THE USE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN TEACHING TECHNOLOGY - Nargiza Niyazmetova; Shahzoda Abduraxmonova Pazliddin qizi (Journals Park Publishing, 2023)
This article discusses innovative pedagogical technologies that can be used to teach technology.
Keywords: Technology, creativity, personality, qualifications, labor, invention.